Australia : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Australia. (IMF Staff Country Reports; Country Report, 2008)
The Article IV Consultation discusses that recently a commodity price boom, driven by robust global demand, has pushed the Australian economy up against capacity constraints. Banks are adjusting the structure of their funding in response to the turmoil, increasing liquidity, and lengthening the maturity of their funding. Executive Directors considered that the sound macroeconomic framework should permit Australia to weather the global downturn and contain inflationary pressures. They encouraged the authorities to take advantage of the positive macroeconomic performance to advance structural reforms.